Pelatihan dan Pendampingan Budidaya Sayur-Sayuran di Luar Musim Agar Petani Mendapatkan Harga Mahal di Desa Lendang Nangka Utara Masbagik, Lombok Timur, Nusa Tenggara Barat - I Ketut Ngawit; Anjar Pranggawan Azhari; Amrul Jihadi (Universitas Mataram, 2026)
Farmers incur losses when they grow tomatoes, chili, sweet corn, spinach, and shallots in the dry season because the prices are low. Growing them in the rainy season is very risky, as these vegetables are sensitive to waterlogged soil. In addition, the skills and abilities of the farmers in the village of Lendang Nangka Utara, Masbagik District, East Lombok, in cultivating off-season vegetables, are still limited. Therefore, training and mentoring are carried out, with the main goal of improving the knowledge and skills of farmers in cultivating off-season vegetables to achieve higher selling prices. After participating in training sessions and direct on-site support, the knowledge and skills of farmers in vegetable cultivation have increasingly improved, as evidenced by the fact that the previously low participation and enthusiasm have increased. The intensive application of some agronomic measures, such as improving soil aeration, using plastic mulch, applying 20–25 tons he-1 of organic fertilizer, and 50–250 kg he-1 NPK Ponska, provides higher yields in Pak Choi, tomatoes, chili, and shallots compared to planting without organic fertilizer, plastic mulch, and soil aeration improvement. The application of organic fertilizer at a dose of 15–25 tons he-1 can replace the role of NPK Ponska fertilizer by 25% to 50% of the dose of 300 kg he-1. The income and profit that farmers earn from growing pak choi, tomatoes, chili, and shallots are higher than those from growing spinach, long beans, and sweet corn.